The relationship between professional self-concept and career decision-making difficulties among postgraduate nursing students in China: the mediating role of career decision-making self-efficacy - Bi, Yaping; Mou, Shaoyu; Wang, Ge; Liao, Mingyan (Frontiers in Psychology, 2023)
Background In the context of a global shortage, uneven distribution, and structural imbalance of nursing talent, postgraduate nursing students must make appropriate decisions about their careers not only for the nursing profession but also for society as a whole. However, little research has been reported on the current status and factors influencing career decision-making difficulties among postgraduate nursing students. Objectives Exploring the mediating role of career decision-making self-efficacy between professional self-concept and career decision-making difficulties among postgraduate nursing students in China based on the social cognitive career theory. Methods 276 postgraduate nursing students from 25 universities in seven administrative regions of China were selected by stratified random sampling. Data were collected with the Career decision-making difficulties Questionnaire, Career Decision-making Self-Efficacy Scale, and Nursing Professional Self-concept Scale through an online survey, and were analyzed by univariate analysis, correlation analysis, multiple linear regression analysis, and PROCESS macro. Results The score for career decision-making difficulties was 2.84 (SD = 0.54). Professional self-concept (r = −0.496, p < 0.01) and career decision-making self-efficacy (r = −0.551, p < 0.01) were negatively associated with career decision-making difficulties. Career decision-making self-efficacy played a partial mediating role between professional self-concept and career decision-making difficulties (p < 0.01), with the mediating effect (Effect Value = −0.253, Bootstrap 95% CI: −0.349, −0.156) accounting for 53.82% of the total effect. Conclusion The high scores of career decision-making difficulties among postgraduate nursing students demand widespread attention. Nursing educators need to develop a complete and standardized career counseling curriculum for postgraduate nursing students, and should pay attention to the cultivation and development of positive professional self-concept and career decision-making self-efficacy of postgraduate nursing students to reduce their career decision-making difficulties and help them make effective career decision-making.